2017
DOI: 10.1007/jhep07(2017)113
|View full text |Cite
|
Sign up to set email alerts
|

Minimal conformal extensions of the Higgs sector

Abstract: In this work we find the minimal extension of the Standard Model's Higgs sector which can lead to a light Higgs boson via radiative symmetry breaking and is consistent with the phenomenological requirements for a low-energy realization of a conformal theory. The model which turns out to be stable under renormalization group translations is an extension of the Standard Model by two scalar fields, one of which acquires a finite vacuum expectation value and therefore mixes into the physical Higgs. We find that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 55 publications
(80 reference statements)
1
54
0
Order By: Relevance
“…Earlier works investigating SI extensions of the SM appear in refs. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and, in particular, studies of SI models for neutrino mass can be found in refs. [82][83][84][85][86][87][88][89][90][91][92].…”
Section: Jhep06(2016)182mentioning
confidence: 99%
“…Earlier works investigating SI extensions of the SM appear in refs. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and, in particular, studies of SI models for neutrino mass can be found in refs. [82][83][84][85][86][87][88][89][90][91][92].…”
Section: Jhep06(2016)182mentioning
confidence: 99%
“…Also, the possibility that neither χ nor Σ 0 acquires a nonzero vacuum expectation value is ruled out due to the appearing of Landau poles below the Planck scale [29]. Thus, we are left with the following two cases 2 :…”
Section: The Modelmentioning
confidence: 99%
“…In [29], it has already been pointed out that replacing a real gauge singlet by a higher-dimensional real SU(2) L multiplet will cause possible Landau poles to appear at higher scales, and hence we will not analyze the stability of the running coupling constants any further. Instead, we restrict our attention on other theoretical and phenomenological consequences of the model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, all the mass scales must be generated by dimensional transmutation such as Coleman-Weinberg mechanism [21]. Though it was found that this mechanism cannot be applied directly to the SM Higgs sector since the predicted Higgs mass ∼ 10 GeV is experimentally excluded, phenomenologically viable models still exist if one includes an additional scalar to the model so that the mass scale comes from the breaking of the conformal invariance of that field [22][23][24][25][26][27] (see also [28] for [25]). In Ref.…”
Section: Introductionmentioning
confidence: 99%